Self-adhesive foam sheet

A thin self-adhesive foam sheet with specific emulsion compositions and structures addresses adhesive and flexibility issues, ensuring high strength and retention for repeated use.

JP7608511B2Active Publication Date: 2025-01-06INOAC TECHN CENT +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023073333
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-01-06
Estimated Expiration
2039-06-04

AI Technical Summary

Technical Problem

Existing self-adhesive foams are not suitable for applications requiring thinness due to issues with adhesive strength, adhesive retention, and flexibility, especially when repeatedly used, leading to potential material destruction and loss of flexibility when made thinner.

Method used

A self-adhesive foam sheet with a thickness of 0.05 to 0.5 mm, containing specific emulsion compositions and properties, including acrylic and ethylene vinyl acetate emulsions, tackifiers, and semi-open cell structures, which are laminated with PET films, ensuring high adhesive strength, retention, and flexibility.

Benefits of technology

The foam sheet maintains excellent adhesive strength, retention, and interlayer peel strength while being flexible and reusable, suitable for applications requiring thinness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608511000002
    Figure 0007608511000002
  • Figure 0007608511000001
    Figure 0007608511000001
Patent Text Reader

Abstract

To provide a self-adhesive foam sheet which is in the form of a thin sheet of 0.05 mm to 0.5 mm, has adhesive strength, adhesive holding power and interlaminar peeling strength as well as flexibility and can be used repeatedly.SOLUTION: There is provided a self-adhesive foam sheet obtained by foaming an emulsion composition comprising an emulsion, a foaming agent and a tackifier by a mechanical floss method, followed by curing, wherein the self-adhesive foam sheet has a thickness of 0.05 to 0.5 mm, the emulsion has a glass transition temperature of -35 to 25°C and the blending amount of the tackifier is 3 to 40 pts.mass when the blending amount of the emulsion is defined as 100 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a self-adhesive foam sheet. [Background technology]

[0002] Conventionally, in order to impart tackiness and adhesiveness to foams, adhesive processing suitable for each application is often performed, such as laminating an adhesive or bonding layer, applying a hot melt adhesive, impregnating with an adhesive, etc. Since a separate process is required to perform adhesive processing suitable for each application, such as laminating an adhesive or bonding tape, applying a hot melt adhesive, impregnating with an adhesive, etc., a self-adhesive foam in which the foam itself has adhesiveness has been proposed (for example, Patent Document 1).

[0003] There are also self-adhesive foams that can be attached to an adherend, peeled off, and then reattached (reused repeatedly). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-37829 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0005] When a self-adhesive foam is used as an adsorption bed material in a house or a commercial facility, there is a concern that if a step occurs, the person may trip or the step surface may be damaged, so a thin self-adhesive foam (sheet) is required. In contrast, as can be seen from paragraph 0061, the self-adhesive foam of Patent Document 1 has a thickness of 3 mm, and is not intended for use in applications where thinness is required. In other words, the self-adhesive foam of Patent Document 1 requires an effect such as absorbing steps due to the flexibility of the foam, so a certain thickness is required and thinning is not taken into consideration.

[0006] Therefore, if the self-adhesive foam of Patent Document 1 is made thin enough to be on the order of millimeters or less, there is a risk that the adhesive strength and adhesive retention will decrease, material failure (interlayer failure) will occur during repeated use, or the foam will become too high density and lose flexibility.

[0007] Therefore, an object of the present invention is to provide a self-adhesive foam sheet that is in the form of a thin sheet of 0.05 mm to 0.5 mm, has high adhesive strength, adhesive retention and interlayer peel strength, and also has flexibility, and can be used repeatedly. [Means for solving the problem]

[0008] The present inventors have conducted extensive research and found that a self-adhesive foam sheet containing specific components and having specific properties can solve the above problems, and have completed the present invention.

[0009] The present invention (1) is A self-adhesive foamed sheet obtained by foaming an emulsion composition containing an emulsion, a foaming agent, and a tackifier by a mechanical froth method and then curing the same, The thickness of the self-adhesive foam sheet is 0.05 to 0.5 mm; The glass transition temperature of the emulsion is −35 to −25° C., The self-adhesive foam sheet is characterized in that the blending amount of the tackifier is 3 to 40 parts by mass relative to 100 parts by mass of the blending amount of the emulsion. The present invention (2) is The self-adhesive foam sheet has an apparent density of 300 to 800 kg / m as measured in accordance with JIS K7222:2005. 3 The self-adhesive foam sheet according to the above invention (1), The present invention (3) is The emulsion includes an acrylic emulsion and an ethylene vinyl acetate emulsion, The blending amount of the acrylic emulsion is 40 to 80% by mass, assuming the mass of all the emulsions to be 100% by mass. The self-adhesive foam sheet according to the invention (1) or (2) is characterized in that the blending amount of the ethylene vinyl acetate emulsion is 20 to 60 mass % when the mass of all the emulsions is 100 mass %. The present invention (4) is The self-adhesive foam sheet is characterized in that when a PET film having a thickness of 38 μm is laminated on both sides of the self-adhesive foam sheet and a T-peel test is performed, the interlayer peel strength of the self-adhesive foam sheet is 3.0 N / 12 mm or more. The self-adhesive foam sheet according to any one of the above inventions (1) to (3). The present invention (5) is The self-adhesive foam sheet according to any one of inventions (1) to (4) is characterized in that the adherend is a BA-finished SUS304 board and the adhesive strength measured in accordance with JIS Z0237 is 1.5 to 3.5 N / 24 mm. The present invention (6) is The self-adhesive foam sheet according to any one of inventions (1) to (5), characterized in that when an adherend is a BA finished SUS304 board, the BA finished SUS304 board is tilted 45° from the vertical, and the self-adhesive foam sheet processed to a length of 50 mm and a width of 24 mm is attached to the underside of the board, and a 200 g weight is hung from the board, the time it takes for the self-adhesive foam sheet to fall is 60 seconds or more. Effect of the Invention

[0010] According to the present invention, it is possible to provide a self-adhesive foam sheet that is in the form of a thin sheet of 0.05 mm to 0.5 mm, has excellent adhesive strength, adhesive retention, and interlayer peel strength, and also has flexibility, and can be used repeatedly. [Brief description of the drawings]

[0011] [Figure 1]FIG. 2 is an explanatory diagram showing a method for measuring the adhesive holding power of the self-adhesive foam sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Here, in the present invention, "self-adhesive" refers to a property in which, due to the nature of the material, the material adheres to the adherend when pressed down, without being coated with an adhesive (including providing an adhesive layer) or impregnated with an adhesive, but can be peeled off from the joint without transferring to the adherend when peeled off.

[0013] In addition, the "semi-open cell structure" is a structure in which the pores (holes) between adjacent cells are smaller than those of open cells, and unlike closed cells, the cells have small pores. The value measured using a Frazier type air permeability tester in accordance with JIS L1096 Method A is 2 [ml / cm 2 / s] or more, 80[ml / cm] 2 / s].

[0014] In the present invention, the term "interlaminar peel strength" is an index of the material strength of the sheet of the present invention, and refers to the stress at the time of tearing in the case of T-shaped peeling. Specifically, the strength can be measured by the test method described later.

[0015] 1.Self-adhesive foam sheet The self-adhesive foam sheet of the present invention is characterized in that it is produced by foaming an emulsion composition containing an emulsion, a foaming agent, and a tackifier by a mechanical froth method, and then curing the foam.

[0016] The self-adhesive foam sheet of the present invention is characterized in that its thickness is 0.05 to 0.5 mm. The thickness of the self-adhesive foam sheet can be changed depending on the application. The thinner the thickness of the self-adhesive foam sheet, the higher the apparent density tends to be, and the higher the interlaminar fracture strength, but the weaker the adhesive strength and adhesive retention. The relationship between thickness and density varies depending on the material used for the self-adhesive foam sheet, and can be adjusted by changing the amount of air mixed in the mechanical floss method or the settings of the doctor knife, doctor roll, etc.

[0017] The self-adhesive foam sheet of the present invention is characterized in that the emulsion used in the self-adhesive foam sheet has a glass transition temperature of -35 to -25°C.

[0018] The method for measuring the glass transition temperature will be described later.

[0019] The self-adhesive foam sheet of the present invention is characterized in that the amount of the tackifier used in the self-adhesive foam sheet is 3 to 40 parts by mass when the amount of the total emulsion is 100 parts by mass. When the amount of the tackifier used in the self-adhesive foam sheet is within this range, a self-adhesive foam sheet can be obtained that is in the form of a thin sheet of 0.05 mm to 0.5 mm, has high adhesive strength, adhesive retention, and interlayer peel strength, and also has flexibility, and can be used repeatedly.

[0020] The structure of the self-adhesive foam sheet of the present invention is not particularly limited, and may include any of a closed cell structure, a semi-open cell structure, and an open cell structure. These may be used alone or in combination. Of these, semi-open cells are preferred. When the self-adhesive foam sheet has a semi-open cell structure, the sheet has a suction cup effect, which allows the sheet to adhere to the adherend, thereby increasing the adhesive strength and adhesive retention.

[0021] The upper and lower limits of the average cell diameter of the cross-section of the self-adhesive foam sheet of the present invention are not particularly limited, but the upper limit of the average cell diameter can be, for example, 100 μm or less, and preferably 50 μm or less. The lower limit of the average cell diameter can be, for example, 0.1 μm or more, and preferably 10 μm or more. When the average cell diameter of the cross-section of the self-adhesive foam sheet is within this range, it is possible to increase the adsorption surface area of ​​the self-adhesive foam sheet, and the adhesive strength and adhesive retention can be increased.

[0022] The average cell diameter is measured according to the following method. First, a scanning electron microscope (SEM, Keyence Corporation, VHXD-500) is used to take a photograph of the cross section of the porous foam layer 110. Then, the image processing software Image-Pro PLUS (Media Cybernetics, 6.3ver) is used to measure the diameter of each bubble (cell). More specifically, the SEM image is read, and the contrast is adjusted to recognize the bubbles (cells) by contrast. Next, the shape of the bubbles (cells) is read by image processing (recognizing the shape as it is, not a perfect circle). Next, "diameter (average)" is selected as the measurement item. Next, the diameter passing through the center of gravity of the object is measured at 2-degree intervals, and the average value is used to calculate the diameter of each bubble (cell).

[0023] The apparent density of the self-adhesive foam sheet of the present invention is not particularly limited, but is, for example, 300 to 800 kg / m 3 and can be set at 400 to 600 kg / m 3 When the apparent density is in this range, combined with the effect of the thickness, it becomes possible to obtain a self-adhesive foamed sheet that has high adhesive strength, adhesive retention, and interlayer peel strength, and also has flexibility, even though it is in the form of a thin sheet of 0.05 mm to 0.5 mm.

[0024] In the present invention, the apparent density is measured in accordance with JIS K7222:2005 "Foamed plastics and rubber - Determination of apparent density".

[0025] The self-adhesive foam sheet of the present invention may be laminated with a film-like substrate or a release-treated resin film.

[0026] The self-adhesive foam sheet of the present invention will be described in detail below.

[0027] 1-1. Emulsion The emulsion according to the present invention has a glass transition temperature of -35 to -25°C.

[0028] Examples of emulsions include acrylic emulsions, urethane emulsions, ethylene vinyl acetate emulsions, vinyl chloride emulsions, epoxy emulsions, etc. These may be used alone or in combination.

[0029] Among these, it is preferable to use an acrylic emulsion because of its excellent adhesive strength, light weight, and heat insulation. Furthermore, it is more preferable to combine this acrylic emulsion with an ethylene vinyl acetate emulsion, since this makes it possible to obtain a self-adhesive foamed sheet in the form of a thin sheet of 0.05 mm to 0.5 mm, which has excellent adhesive strength, adhesive retention, and interlayer peel strength, and also has flexibility.

[0030] The acrylic emulsion can be produced by copolymerizing, for example, a (meth)acrylic acid ester monomer as an essential polymerizable monomer component, and, if necessary, a mixture of other polymerizable monomers copolymerizable with these monomers, in the presence of a polymerization initiator and, if necessary, an emulsifier and a dispersion stabilizer.

[0031] Polymerizable monomers that can be used in the preparation of acrylic emulsions include (meth)acrylic acid ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, octadecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, phenyl (meth)acrylate, and benzyl (meth)acrylate; acrylic acid, methacrylic acid, β-carboxyethyl (meth)acrylate, 2-(meth)acryloylpropionic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, and itaconic acid. Examples of the monomers include unsaturated bond-containing monomers having a carboxyl group such as half ester, maleic acid half ester, maleic anhydride, and itaconic anhydride; glycidyl group-containing polymerizable monomers such as glycidyl (meth)acrylate and allyl glycidyl ether; hydroxyl group-containing polymerizable monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and glycerol mono(meth)acrylate; ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, diallyl phthalate, divinylbenzene, and allyl (meth)acrylate. These may be used alone or in combination.

[0032] When an emulsifier is used in preparing the acrylic emulsion, a known emulsifier can be used.

[0033] Ethylene vinyl acetate emulsions can be produced, for example, by copolymerizing ethylene and vinyl acetate monomers by emulsion polymerization using polyvinyl alcohol or the like as a protective colloid and a cellulose derivative such as hydroxyethyl cellulose or a surfactant as an emulsifying and dispersing agent.

[0034] The ethylene vinyl acetate emulsion may be one further copolymerized with a vinyl monomer having a functional group such as a carboxyl group, an epoxy group, a sulfonic acid group, a hydroxyl group, a methylol group, or an alkoxy group.

[0035] The blending amount of the acrylic emulsion and the ethylene vinyl acetate emulsion when combined is not particularly limited as long as it does not impair the effects of the present invention. For example, the blending amount of the acrylic emulsion and the ethylene vinyl acetate emulsion when combined can be 40 to 80% by mass as the acrylic emulsion and 20 to 60% by mass as the ethylene vinyl acetate emulsion, when the mass of the total emulsion is 100% by mass.

[0036] The ratio of the amount of the acrylic emulsion to the amount of the ethylene vinyl acetate emulsion (amount of the acrylic emulsion / amount of the ethylene vinyl acetate emulsion) is not particularly limited, but may be, for example, 0.1 to 10.0, preferably 0.67 to 4.0, and more preferably 1.5 to 4.0. By setting the ratio of the amount of the acrylic emulsion to the amount of the ethylene vinyl acetate emulsion within this range, a self-adhesive foamed sheet can be obtained that is in the form of a thin sheet of 0.05 mm to 0.5 mm, has excellent adhesive strength, adhesive retention, and interlayer peel strength, and also has flexibility.

[0037] In the present invention, the dispersion medium of the emulsion composition is essentially water, but may be a mixture of water and a water-soluble solvent. The water-soluble solvent may be, for example, alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, ethyl carbitol, ethyl cellosolve, butyl cellosolve, etc., polar solvents such as N-methylpyrrolidone, etc., and one or a mixture of two or more of these may be used.

[0038] Among the emulsions used in the present invention, the physical properties of the acrylic emulsion and the ethylene vinyl acetate emulsion, which are preferred embodiments, will be described below.

[0039] ·Viscosity (mPa s) The viscosity is measured by a Brookfield viscometer (25° C.).

[0040] The viscosity of the acrylic emulsion is preferably 5,000 to 20,000 mPa·s. It is more preferably 8,000 to 15,000 mPa·s. If the viscosity is 5,000 mPa·s or more, the bubble retention during molding is sufficient, finer cells can be formed, and the adhesive strength tends to be stronger. Conversely, if the viscosity is 20,000 mPa·s or less, the shear force on the raw material during molding can be reduced, preventing the formation of distorted cells, and more sufficient adhesive strength can be obtained.

[0041] The viscosity of the ethylene vinyl acetate emulsion is preferably 2,000 to 4,000 mPa s, and more preferably 2,000 to 3,000 mPa s. If the viscosity is within this range, when combined with the acrylic emulsion, it is believed that the stirring efficiency is increased, the vinyl acetate is uniformly distributed, and stronger adhesive strength and material strength can be exhibited.

[0042] More specifically, the stirring efficiency is considered to be one of the important factors in the formation of bubbles when produced by the mechanical flossing method. The increase in the stirring efficiency makes it possible to form the bubbles in the raw material into finer and more uniform bubbles. This increases the adhesion area to the adherend, which is considered to improve the adhesive strength to the adherend. It is also assumed that this affects the strong suction effect brought about by the fine cells.

[0043] Glass transition temperature The glass transition temperature is determined as the peak value of tan δ measured using a dynamic viscoelasticity measuring device (DMA, model MCR302, manufactured by Anton Paar) according to the procedure in accordance with JIS K7198, under conditions of -80°C to 150°C, heating at 5°C / min, and 1 Hz.

[0044] It is also preferable that the glass transition temperatures of the acrylic emulsion and the ethylene vinyl acetate emulsion are both −10° C. or lower. This is because the acrylic resin and ethylene vinyl acetate tend to become highly hard and lose adhesion when used at low temperatures.

[0045] ·others Regarding acrylic emulsions, filler-free ones are more suitable. The reason for this is presumably that filler-free emulsions can achieve low hardness (impart flexibility) and improve conformability to the adherend.

[0046] 1-2.Foaming agent The emulsion composition according to the present invention contains a foaming agent. The foaming agent according to the present invention is not particularly limited as long as it does not inhibit the effects of the present invention. Examples of foaming agents include animal protein surfactants such as casein, glue, and albumin, anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants. These can be used alone or in combination. Among these, it is preferable to contain an anionic surfactant because it has low foaming properties, and it is more preferable to contain an anionic surfactant and an amphoteric surfactant because the bubbles are fine and uniform.

[0047] Specific examples of anionic surfactants include sodium laurate, sodium myristate, sodium stearate, ammonium stearate, sodium oleate, potassium oleate soap, potassium castor oil soap, potassium coconut oil soap, sodium lauroyl sarcosine, sodium myristoyl sarcosine, sodium oleyl sarcosine, sodium cocoyl sarcosine, sodium coconut alcohol sulfate, sodium polyoxyethylene lauryl ether sulfate, sodium alkyl sulfosuccinate, sodium lauryl sulfoacetate, sodium alkylbenzene sulfonate, and sodium α-olefin sulfonate, with sodium alkyl sulfosuccinate being particularly preferred.

[0048] Here, in order to facilitate dispersion in the emulsion composition, the anionic surfactant used in this embodiment preferably has an HLB of 10 or more, more preferably 20 or more, and particularly preferably 30 or more.

[0049] ·HLB In the present invention, the HLB value means a hydrophilic-hydrophobic balance (HLB) value, and is determined by the Oda method. The method for determining HLB by the Oda method is described in "New Surfactant Introduction" pp. 195-196 and "Synthesis and Application of Surfactants" by Oda Ryohei et al., published by Maki Shoten on March 20, 1957, pp. 492-502, and can be calculated as HLB = (inorganic / organic) x 10.

[0050] (Amphoteric surfactant) The emulsion composition of the present invention uses an amphoteric surfactant in addition to an anionic surfactant, thereby making the air bubbles fine and uniform.

[0051] In particular, when an anionic surfactant and an amphoteric surfactant are used in combination, the charges of the hydrophilic groups of the anionic surfactant molecules repel each other, and while the anionic surfactant molecules are kept at a certain distance from each other, the electrically neutral amphoteric surfactant enters between the anionic surfactant molecules, thereby making the bubbles more stable and reducing the size of the bubbles. This can improve the interlayer peel strength. Therefore, it is preferable to use an anionic surfactant and an amphoteric surfactant in combination.

[0052] The amphoteric surfactant according to the present invention is not particularly limited, and may be an amino acid type, a betaine type, an amine oxide type, or other amphoteric surfactant. A betaine type amphoteric surfactant is preferable because it has a higher effect as described above. Furthermore, from the viewpoint of ease of incorporation between the molecules of an anionic surfactant, C10-12 amphoteric surfactants are preferable.

[0053] Examples of the amino acid type amphoteric surfactant include N-alkyl or alkenyl amino acids or salts thereof. N-alkyl or alkenyl amino acids have a structure in which an alkyl or alkenyl group is bonded to a nitrogen atom, and one or two groups represented by "-R-COOH" (wherein R represents a divalent hydrocarbon group, preferably an alkylene group, and particularly preferably has 1 to 2 carbon atoms) are bonded to the nitrogen atom. In a compound with one "-R-COOH" bonded, a hydrogen atom is further bonded to the nitrogen atom. A compound with one "-R-COOH" is called a mono-form, and a compound with two "-R-COOH"s is called a di-form. Either of these mono-forms or di-forms can be used as the amphoteric surfactant of the present invention. In the N-alkyl or alkenyl amino acid, the alkyl or alkenyl group may be linear or branched. Specific examples of amino acid type amphoteric surfactants include sodium lauryldiaminoethylglycine, sodium trimethylglycine, sodium cocoyl taurate, sodium methyl cocoyl taurate, sodium lauroyl glutamate, potassium lauroyl glutamate, and lauroyl methyl-β-alanine.

[0054] Examples of betaine-type amphoteric surfactants include alkyl betaines, imidazolinium betaines, carbobetaines, amido carbobetaines, amido betaines, alkyl amido betaines, sulfobetaines, amido sulfobetaines, phosphobetaines, etc. Specific examples of betaine-type amphoteric surfactants include lauryl betaine, stearyl betaine, lauryl dimethylamino acetic acid betaine, stearyl dimethylamino acetic acid betaine, lauric acid amido propyl dimethylamino acetic acid betaine, isostearic acid amido ethyl dimethylamino acetic acid betaine, isostearic acid amido propyl dimethylamino acetic acid betaine, isostearic acid amido ethyl diethylamino acetic acid betaine, isostearic acid amido propyl diethylamino acetic acid betaine, isostearic acid amido ethyl dimethylamino hydroxysulfobetaine, isostearic acid amido propyl dimethylamino hydroxysulfobetaine, isostearic acid amido ethyl diethylamino hydroxysulfobetaine, isostearic acid amido propyl diethylamino hydroxysulfobetaine, isostearic acid amido ethyl diethylamino hydroxysulfobetaine, isostearic acid amido propyl diethylamino hydroxysulfobetaine, N-lauryl-N,N -dimethylammonium-N-propyl sulfobetaine, N-lauryl-N,N-dimethylammonium-N-(2-hydroxypropyl) sulfobetaine, N-lauryl-N,N-dimethyl-N-(2-hydroxy-1-sulfopropyl)ammonium sulfobetaine, lauryl hydroxysulfobetaine, dodecylaminomethyl dimethyl sulfopropyl betaine, octadecylaminomethyl dimethyl sulfopropyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine (2-lauryl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine 2-stearyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, etc.), coconut oil fatty acid amidopropyl betaine, coconut oil fatty acid amidopropyl hydroxysultaine, etc.

[0055] Examples of the amine oxide type amphoteric surfactant include lauryl dimethylamine-N-oxide and oleyl dimethylamine-N-oxide.

[0056] Among the above-mentioned amphoteric surfactants, it is preferable to use betaine-type amphoteric surfactants in the method for producing an emulsion composition according to the present invention, and among the betaine-type surfactants, alkyl betaines, imidazolinium betaines, and carbobetaines are particularly preferable. Examples of alkyl betaines that can be used in the present invention include stearyl betaine and lauryl betaine, and examples of imidazolinium betaines include 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine.

[0057] 1-3. Tackifier The emulsion composition according to the present invention includes a tackifier. The tackifier is not particularly limited as long as it does not impair the effects of the present invention. Examples of the tackifier include natural resins such as rosin-based resins and terpene-based resins; synthetic resins such as petroleum resins, hydrogenated petroleum resins, styrene-based resins, coumarone-indene-based resins, phenol-based resins, and xylene resins. Examples of the rosin-based resins include rosins such as gum rosin, tall oil rosin, and wood rosin; modified rosins such as hydrogenated rosin, disproportionated rosin, and polymerized rosin; and rosin esters such as glycerin esters and pentaerythritol esters of these rosins and modified rosins. Examples of the terpene-based resins include terpene resins mainly composed of α-pinene, β-pinene, dipentene, etc., aromatic modified terpene resins, hydrogenated terpene resins, and terpene phenol resins. Examples of (hydrogenated) petroleum resins include (hydrogenated) aliphatic (C5) petroleum resins, (hydrogenated) aromatic (C9) petroleum resins, (hydrogenated) copolymer (C5 / C9) petroleum resins, (hydrogenated) dicyclopentadiene petroleum resins, and alicyclic saturated hydrocarbon resins. Examples of the styrene resins include poly-α-methylstyrene, α-methylstyrene / styrene copolymers, styrene monomer / aliphatic monomer copolymers, styrene monomer / α-methylstyrene / aliphatic monomer copolymers, styrene monomer copolymers, and styrene monomer / aromatic monomer copolymers other than styrene monomers. These can be used alone or in combination. Among these, rosin resins are preferred because they have good compatibility with emulsions. Rosin resins have particularly good compatibility with acrylic emulsions and ethylene vinyl acetate emulsions, which are suitable emulsions.

[0058] The softening temperature of the tackifier according to the present invention is not particularly limited. The softening temperature of the tackifier can be, for example, 25 to 200°C, and is preferably 25 to 160°C. When the softening temperature of the tackifier is within this range, a self-adhesive foam sheet having excellent adhesive strength, adhesive retention, and interlayer peel strength, as well as flexibility, can be obtained. From the viewpoint of the interlayer peel strength of the self-adhesive foam sheet, the softening temperature is preferably 80 to 160°C.

[0059] The softening temperature is measured using a differential scanning calorimeter (DSC) measuring device. The softening temperature is measured by increasing the temperature to 25°C to 230°C at a temperature increase rate of 20°C / min, and then decreasing the temperature to 230°C to 25°C at a temperature decrease rate of 5°C / min, and the softening temperature is determined as the peak top temperature of the temperature decrease curve.

[0060] The amount of the tackifier may be 3 to 40 parts by mass, preferably 5 to 40 parts by mass, and more preferably 5 to 30 parts by mass, when the amount of the entire emulsion is taken as 100 parts by mass. When the amount of the tackifier is within this range, a self-adhesive foam sheet having excellent adhesive strength, adhesive retention, and interlayer peel strength, as well as flexibility, can be obtained.

[0061] 1-4.Other ingredients The emulsion composition according to the present invention may contain other components. The other components are not particularly limited as long as they do not impair the effects of the present invention, and examples thereof include a foam stabilizer, a foam stabilizer, a crosslinking agent (curing agent), a catalyst, an antioxidant, an ultraviolet absorber, a thickener, a plasticizer, an antibacterial agent, a colorant, etc. These may be used alone or in combination.

[0062] By using a crosslinking agent (curing agent), it is possible to improve the interlaminar strength of the self-adhesive foam sheet of the present invention.

[0063] The crosslinking agent is not particularly limited as long as it does not impair the effects of the present invention, and may be added in a required amount depending on the application, etc. The crosslinking method using a crosslinking agent includes, for example, physical crosslinking, ionic crosslinking, and chemical crosslinking, and the crosslinking method can be selected according to the type of water-dispersible resin. As the crosslinking agent, a known crosslinking agent can be used, and an epoxy-based crosslinking agent, a melamine-based crosslinking agent, an isocyanate-based crosslinking agent, a carbodiimide-based crosslinking agent, an oxazoline-based crosslinking agent, etc. can be used in an appropriate amount according to the type and amount of functional groups contained in the resin blend used. In order to improve the adhesive strength, tack strength, and interlayer peel strength, an epoxy-based crosslinking agent and an isocyanate-based crosslinking agent are preferred. Isocyanate-based and epoxy-based crosslinking agents can prevent material destruction of the adherend and the self-adhesive foam sheet by increasing the material strength. Among them, aliphatic isocyanates are more preferred. These can be used alone or in combination.

[0064] 2. Manufacturing method of self-adhesive foam sheet The method for producing a self-adhesive foam sheet according to the present invention includes a raw material preparation step, and a foaming / curing step (a step of foaming an emulsion composition containing at least an emulsion and a foaming agent by using a mechanical froth method to form a foam, and curing the foam). The emulsion composition may further contain a crosslinking agent, and in the step, energy may be applied to crosslink the resin constituting the emulsion via the crosslinking agent, thereby curing the foam. Each step will be described in detail below.

[0065] 2-1. Raw material preparation process In the raw material preparation step, the raw materials as described above are mixed to prepare an emulsion composition, which is a raw material mixture for the foam. The mixing method at this time is not particularly limited, but for example, the components may be mixed while stirring in a container such as a mixing tank for mixing the components.

[0066] 2-2. Foaming and curing process In the foaming and curing step, a predetermined foaming gas is added to the emulsion composition obtained in the raw material preparation step, and they are thoroughly mixed to produce a state in which a large number of bubbles exist in the emulsion composition (foamed emulsion composition). This foaming and curing step is usually carried out by thoroughly mixing the raw material mixture of the liquid self-adhesive foamed sheet obtained in the raw material preparation step with the foaming gas using a mixing device such as a mixing head.

[0067] ·Foaming gas The foaming gas mixed into the emulsion composition in the stirring and foaming process forms bubbles (cells) in the foam, and the amount of the foaming gas mixed in determines the expansion ratio and density of the resulting foam. In order to adjust the density of the self-adhesive foam sheet, the weight of the raw material of the self-adhesive foam sheet required is calculated from the desired density of the self-adhesive foam sheet and the volume of the raw material of the self-adhesive foam sheet (for example, the internal volume of the mold into which the raw material of the self-adhesive foam sheet is injected), and the amount of the foaming gas is determined so that the desired volume is obtained at this weight. In addition, air is mainly used as the type of foaming gas, but other inert gases such as nitrogen, carbon dioxide, helium, and argon can also be used.

[0068] Foaming method and conditions The foaming method used in the foam preparation method of the present invention is a mechanical froth method. The mechanical froth method is a method in which air in the atmosphere is mixed into the emulsion composition by stirring the emulsion composition with a stirring blade or the like to foam the emulsion composition. As the stirring device, a stirring device generally used in the mechanical froth method can be used without any particular limitation, and for example, a homogenizer, a dissolver, a mechanical froth foaming machine, etc. can be used. According to this mechanical froth method, a self-adhesive foamed sheet with a density suitable for various applications can be obtained by adjusting the mixing ratio of the emulsion composition and the air. It is also possible to use other foaming methods in combination, but it is not preferable to use a foaming method using a chemical foaming agent in combination because the density increases due to the high ratio of closed bubbles, and the flexibility of the self-adhesive foamed sheet is lost.

[0069] The time for mixing the emulsion composition with air is not particularly limited, but is usually 1 to 10 minutes, preferably 2 to 6 minutes. The mixing temperature is also not particularly limited, but is usually room temperature. The stirring speed in the above mixing is preferably 200 rpm or more (more preferably 500 rpm or more) in order to make the bubbles finer, and is preferably 2000 rpm or less (more preferably 800 rpm or less) in order to smoothly discharge the foam from the foaming machine.

[0070] Foam formation The emulsion composition foamed as described above (foamed emulsion composition) is formed into a foam such as a sheet having a desired thickness by known means such as a doctor knife or a doctor roll.

[0071] ·Cure A known method can be used as a method for hardening the foam. The foam according to the present embodiment can be self-crosslinked, but the foam may be hardened by applying energy to crosslink the resin constituting the emulsion via a crosslinking agent. The step of applying energy is not particularly limited, but may be, for example, a heating step (thermal crosslinking).

[0072] In the heating step, the dispersion medium in the molded foamed emulsion composition is evaporated. The drying method at this time is not particularly limited, but for example, hot air drying may be used. In addition, the drying temperature and drying time are also not particularly limited, but for example, it is sufficient to set it at about 80°C for about 1 to 3 hours.

[0073] In addition, in this heating step, the dispersion medium evaporates from the foamed emulsion composition, and the path through which this steam escapes is connected from the inside to the outside of the self-adhesive foam sheet. Therefore, in the foam according to this embodiment, the path through which this steam escapes remains as open cells, so that at least a part of the bubbles present in the self-adhesive foam sheet becomes open cells. Here, if the foaming gas mixed in the stirring and foaming step remains as it is, the bubbles become closed cells in the obtained self-adhesive foam sheet, and if the mixed foaming gas is connected when the steam escapes in this step, the bubbles become open cells in the obtained self-adhesive foam sheet.

[0074] When a crosslinking agent is added, the heating step advances and completes the crosslinking (curing) reaction of the raw materials. Specifically, the raw materials are crosslinked with each other by the above-mentioned crosslinking agent, and a cured self-adhesive foamed sheet is formed. The heating means at this time is not particularly limited as long as it can sufficiently heat the raw materials and crosslink (cur) the raw materials, and for example, a tunnel-type heating furnace or the like can be used. In addition, the heating temperature and heating time may be any temperature and time that can crosslink (cur) the raw materials, and may be, for example, 80 to 150°C (particularly, about 120°C is preferable) for about 1 hour.

[0075] 3. Characteristics of self-adhesive foam sheet · Interlaminar peel strength (material strength) The interlayer peel strength (material strength) is evaluated by measuring the stress when the sample is T-peeled. Specifically, the self-adhesive foam sheet is processed to a width of 12 mm and a length of 150 mm, and a double-sided tape (manufactured by Nitto Denko Corporation, product number 5000NS) is applied to both sides of the self-adhesive foam sheet, and a backing film (PET film: manufactured by Toray Industries, product number S38, thickness 38 μm) of width 12 mm and length 200 mm is applied to both sides of the self-adhesive foam sheet, and the backing film is pressed by rolling it back and forth twice with a 2 kg roller and left in an oven at 85 ° C for 24 hours. After that, the backing film is left at room temperature (23 ± 5 ° C, 60 ± 20% RH) for more than 1 hour, and the T-peel test force is measured by pulling the backing film at a speed of 1000 mm / min under an environment of room temperature (23 ± 5 ° C, 60 ± 20% RH) using an autograph (manufactured by Shimadzu Corporation, model number AG-X), and the interlayer peel strength (N / 12 mm) is evaluated. The interlayer peel strength is preferably 3.0N / 12mm or more, more preferably 4.0N / 12mm or more, and even more preferably 7.0N / 12mm or more. When the interlayer peel strength is within this range, a self-adhesive foam sheet can be obtained that does not cause material destruction (interlayer destruction) when peeled off from an object. This is because the self-adhesive foam sheet can be peeled off from the object surface without causing material destruction (interlayer destruction), and thus can be used repeatedly.

[0076] Adhesive strength (90° peel strength) The adhesive strength (90° peel strength) is evaluated according to JIS Z0237 by processing the self-adhesive foam sheet to a width of 24 mm x length of 150 mm, attaching a single-sided adhesive tape to the surface (non-adhesive side) to eliminate the effect of stretching, attaching the self-adhesive foam sheet to a 30 mm wide x 200 mm long x 3 mm thick SUS304 BA finish plate, pressing it back and forth twice with a 2 kg roller, and leaving it at room temperature (23±5°C, 60±20% RH) for 24 hours. After that, using an autograph, measure the test force (90° peel) at a speed of 300 mm / min under room temperature (23±5°C, 60±20% RH), and evaluate it as the adhesive strength (90° peel strength) (N / 24 mm). The adhesive strength is preferably 0.4 to 2.5 N / 24 mm, more preferably 0.9 to 2.5 N / 24 mm, and even more preferably 1.1 to 2.5 N / 24 mm. When the adhesive strength is within this range, a self-adhesive foam sheet can be obtained that has sufficient adhesive strength and does not cause material destruction (interlayer destruction) when peeled off from an object. This is because the self-adhesive foam sheet can be peeled off from the object surface without causing material destruction (interlayer destruction), and thus can be used repeatedly.

[0077] ·Adhesive holding power The adhesive retention is measured by the following method using the device shown in Figure 1. The self-adhesive foam sheet is punched out to 24 mm wide x 50 mm long, and the self-adhesive foam sheet with one-sided adhesive tape attached to the surface (non-adhesive side) to eliminate the effect of stretching is attached to a 300 mm wide x 300 mm long x 5 mm thick SUS304 BA finish plate, and pressed twice with a 2 kg roller to form a test piece, which is left at room temperature (23 ± 5 ° C, 60 ± 20% RH) for 24 hours. After that, the SUS304 BA finish plate is tilted 45 ° to the vertical direction as shown in Figure 1, a 200 g weight is hung on the self-adhesive foam sheet on its underside, and the time until the test piece falls is measured to evaluate the adhesive retention. The retention time can be 60 seconds or more, and is preferably 180 seconds or more. There is no upper limit to the retention time.

[0078] 4.Applications of self-adhesive foam sheet The self-adhesive foam sheet of the present invention can be used in places where thickness is limited, i.e., where thinness is required, such as in automobiles, building materials, and electronics, and can be used as a joining member that can be repeatedly attached and detached. EXAMPLES

[0079] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "%" representing the content means % by mass.

[0080] <Foam raw materials> First, in this example, the following raw materials were used as the raw materials for the foam. <Emulsion> Acrylic emulsion: solids concentration 54%, Tg -20℃, viscosity 15,000mPa s Ethylene vinyl acetate emulsion (S3950): Solids concentration 60%, Tg -60℃, viscosity 3,000mPa s <Tackifier> Tackifier 1: Rosin-based tackifier, softening temperature 25℃ Tackifier 2: Rosin-based tackifier, softening temperature 80℃ Tackifier 3: Rosin-based tackifier, softening temperature 100℃ Tackifier 4: Rosin-based tackifier, softening temperature 160℃ <Foaming agent> Anionic foaming agent 1: Sodium alkyl sulfosuccinate, pH 9.4, solids 30%, HLB 39.7 Anionic foaming agent 2: Alkyl betaine, fatty acid alkaminol amide, diethanolamine, anionic surfactant mixture, pH 7, solids 40% Amphoteric foaming agent: Alkyl betaine, pH 10, solids 40% <Other ingredients> · Crosslinking agent: HDI isocyanurate (functional group number 3.5) Solid content 100%

[0081] [Foam raw materials] As the foam raw material of Example 1, acrylic emulsion and ethylene vinyl acetate emulsion were used as the main ingredients, and the total amount of emulsion was taken as the standard (the sum of the solid content and non-solid content was 100 parts by weight), and 5 parts by weight of tackifier 4, 3 parts by weight of anionic foaming agent 1, 3 parts by weight of anionic foaming agent 2, 1 part by weight of amphoteric foaming agent, and 2 parts by weight of crosslinking agent were mixed with 60 (acrylic emulsion):40 (ethylene vinyl acetate emulsion) parts by weight to prepare the foam raw material. The foam raw materials of Examples 2 to 13 and Comparative Examples 1 to 7 were prepared in the same manner as the foam raw material of Example 1, except that the raw materials were mixed in the ratios shown in Table 1.

[0082] [Sheet formation] In each example and comparative example, an inert gas such as air or nitrogen gas was added to the foam raw material, foamed by the mechanical froth method (foaming condition 100 to 1000 rpm), cast on a PET release liner, and then heat-treated (in an oven or drying furnace) to obtain a self-adhesive foam sheet of each example and comparative example. The density of each example and comparative example was adjusted by changing the injection amount of inert gas such as air or nitrogen gas, the rotation speed of the mixer, and the drying conditions. The thickness of the self-adhesive foam sheet of each example and comparative example was set to the thickness shown in Table 1.

[0083] [Evaluation test] Next, the measurements and evaluations of Examples 1 to 13 and Comparative Examples 1 to 7 are shown in Table 1.

[0084] Thickness The thickness was measured by a thickness gauge.

[0085] Apparent density The apparent density was measured in accordance with JIS K7222:2005 "Foamed plastics and rubber - Determination of apparent density".

[0086] · Interlaminar peel strength (material strength) The self-adhesive foamed sheets of each Example and Comparative Example were punched out to a width of 12 mm and a length of 150 mm, and a double-sided tape (manufactured by Nitto Denko Corporation, product number 5000NS) was attached to both sides of the foam, and a backing film (PET film: manufactured by Toray Industries, product number S38) of width 12 mm and length 200 mm was attached to both sides of the punched out foam. The backing film was pressed by rolling it back and forth twice with a 2 kg roller and left in an oven at 85 ° C for 24 hours. After that, the backing film was left at room temperature (23 ± 5 ° C, 60 ± 20% RH) for more than 1 hour, and the test force of pulling the backing film (T-shaped peeling) was measured at a speed of 1000 mm / min under an environment of room temperature (23 ± 5 ° C, 60 ± 20% RH) using an autograph (manufactured by Shimadzu Corporation, model number AG-X). The evaluation criteria were as follows. The results are shown in Table 1. Evaluation criteria ◎: 4.0N / 12mm or more ○: 3.0N / 12mm or more, less than 4.0N / 12mm ×: Less than 3.0N / 12mm

[0087] Adhesive strength (90° peel strength) The self-adhesive foam sheets of each Example and Comparative Example were punched out to a width of 24 mm x length of 150 mm according to JIS Z0237, and a one-sided adhesive tape was attached to the surface (non-adhesive side) to eliminate the effect of elongation. The self-adhesive foam sheets were attached to a BA-finished plate of SUS304 with a width of 30 mm x length of 200 mm x thickness of 3 mm, pressed back and forth twice with a 2 kg roller, and left at room temperature (23±5°C, 60±20% RH) for 24 hours. After that, the test force of pulling up at a speed of 300 mm / min (90° peeling) was measured using an autograph under an environment of room temperature (23±5°C, 60±20% RH). The evaluation criteria were as follows, and the results are shown in Table 1. Evaluation results ○: 1.5N / 12mm or more ×: Less than 1.5N / 12mm

[0088] ·Adhesive holding power The adhesive holding power of each Example and Comparative Example was measured by the following method using the device shown in FIG. 1. The self-adhesive foam sheet of each Example and Comparative Example was punched out to 24 mm wide x 50 mm long, and the self-adhesive foam sheet with one-sided adhesive tape attached to the surface (non-adhesive surface) to eliminate the effect of stretching was attached to a 300 mm wide x 300 mm long x 5 mm thick SUS304 BA finish plate, and pressed twice with a 2 kg roller to form a test piece, which was left at room temperature (23±5°C, 60±20% RH) for 24 hours. Thereafter, the SUS304 BA finish plate was inclined at 45° to the vertical direction as shown in FIG. 1, a 200 g weight was hung on the self-adhesive foam sheet on its underside, and the time until the test piece fell was measured to evaluate the adhesive holding power. The evaluation criteria were as follows, and the evaluation results are shown in Table 1. Evaluation results ◎:200sec. or more ○: 60 sec. or more and less than 200 sec. ×: Less than 60 sec.

[0089] ·comprehensive evaluation ◎: No × and two or more ◎ in the above evaluation results ○: No × and less than two ◎ in the above evaluation results. ×: The above evaluation results show ×

[0090] [Table 1] [Explanation of symbols]

[0091] 1 Adhesive retention force measuring device 10 SUS304BA Finish Plate 20 Single-sided adhesive tape 30 Self-adhesive foam sheet 40 weight

Claims

[Claim 1] A self-adhesive foam sheet having a thickness of 0.05 to 0.5 mm, the self-adhesive foam sheet being made from acrylic emulsion and ethylene vinyl acetate emulsion as raw materials, When a PET film having a thickness of 38 μm is laminated on both sides of the self-adhesive foam sheet and a T-peel test is performed, the interlayer peel strength of the self-adhesive foam sheet is 3.0 N / 12 mm or more; The self-adhesive foam sheet has an adhesive strength of 1.5 to 3.5 N / 24 mm as measured in accordance with JIS Z0237 on an adherend made of a BA-finished SUS304 board; The self-adhesive foam sheet has an adherend made of a BA-finished SUS304 board, the BA-finished SUS304 board is tilted at 45° from the vertical, the self-adhesive foam sheet processed to a length of 50 mm and a width of 24 mm is attached to the underside of the board, and a weight of 200 g is hung from the board. The time it takes for the self-adhesive foam sheet to fall is 60 seconds or more. A self-adhesive foam sheet.

Citation Information

Patent Citations

  • Dust adsorbing sheet, dust adsorbing roll and dust adsorbing mat

    JP1996266460A

  • Self-adhesive foam

    JP2002037829A

  • Surface protective sheet and method for manufacturing it

    JP2003001741A

  • Laminate sheet and manufacturing method of the same

    JP2016120710A

  • Manufacturing method of adhesive sheet

    JP2016121312A